Comparison of Sharia Economic Law Thoughts Oni Syahroni and Erwandi Tarmizi on Administration Fees and Discounts on E-Money - ASHFAHANY, AFIEF EL; RINDIANI, LIFIA; HAKIM, LUKMANUL (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This paper tries to find out the thoughts of Sharia Economic Law by Dr Oni Sahroni, MA and Dr. Erwandi Tarmizi, MA on E-money applications in theory and practice such as administrative costs and the practice of discount. This research is library research with the data collected through qualitative domain analysis. The data analysis techniques used are data reduction, data display and data verification. The study findings are as follows: (1) Both agreed that the use of E-money is currently allowed if there is a Semi-Emergency (Hajjah) situation and it is used appropriately if there is Udzur since the majority of E-money currently available does not meet the criteria of DSN MUI fatwa; (2) Administration Fee in E-money is allowed as long as the costs incurred are actual costs; (3) Dr. Oni Sahroni stated that the discount on E-money was legally allowed if there is no preconditions followed, while Dr. Erwandi Tarmizi suggested not using a digital wallet at a discount because the discount used for payment could be in the form of interest.